Chapter Por uma Europa com vontade de futuro - Abreu, Luís (Libere carte, 2023)
The Europe of the future, democratic, freedom fighter, promoter of peace and well-being, is a task of all Europeans. The founding fathers of the European project opened up the path that men of good-will like David Sassoli were capable of dynamizing with determination and wisdom. It is important to follow their example and make of the general interest of Europe the common wish of each citizen and each nation.